The Romanian consumer's perception on the whole grains market: Opportunities and barriers consumption - Ruxandra-Eugenia Pop; Alecsandra Rusu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
Within the internal research plan of the Research Institute for Agrarian Economy and Rural Development, runs the project entitled "Marketing studies for sustainable agri-food products and consumption behavior analysis, in the European Strategy from farm to Fork objectives context". This paper presents the main results obtained in phase 4 of the mentioned project, phase in which the whole grain market was analyzed, through specific marketing, qualitative and quantitative research methods. In order to fulfill the objectives of the research, a questionnaire was applied to a sample of 126 respondents, with the aim of determining the preferences of Romanian whole grains consumers. During the interpretation of the obtained results, similarities with other studies in the field carried out on this market were highlighted, but also particularities, specific to the Romanian market, depending on the socio-demographic characteristics of the consumer. With a slow growing specific products consumption in the reference market, it is observed that the traditional consumption habits formed since childhood constitute the main barrier to the replacement of conventional products obtained from the grains processing with whole grains products, for each of us. Moreover, regardless of the product, consumption habits and consumer perception represent consumption coordinates that are difficult to change, no matter how effective the marketing strategy is implemented.
Keywords: M31; C12; 330; marketing; From Farm to Fork; consumer behavior; whole grain market